The Values of Interdisciplinarity in Homicide Law Reform - Weisberg, Robert (2009)
Professor Reid Fontaine's article, Adequate (Non)Provocation and Heat of Passion as Excuse Not Justification, makes a convincing case for treating heat of passion wholly as an excuse not a justification, as the only sensible way to comprehend its various forms. In doing so, Professor Fontaine stimulates further thinking about heat of passion doctrine, along two dimensions